Does Intramedullary Reaming in Total Knee Arthroplasty Increase Postoperative Bleeding? A Propensity Score–Matched Cohort Study - Sachiyuki Tsukada, MD, PhD; Hiroyuki Ogawa, MD; Masayoshi Saito, MD; Masahiro Nishino, MD; Takuya Kusakabe, MD, PhD; Naoyuki Hirasawa, MD, PhD (Arthroplasty Today)
Background: There is conflicting evidence about whether avoiding medullary canal reaming of the femur during total knee arthroplasty (TKA) reduces blood loss. This study aimed to test the hypothesis that total blood loss would decrease in TKA without medullary canal reaming. Method: This propensity score–matched cohort study included 349 patients, of whom 220 underwent TKA using a femoral intramedullary rod, and 129 underwent TKA using a computer-assisted system without a femoral intramedullary alignment system. For the proximal tibia resection, an intramedullary alignment system was not used in any of the patients. These patients were matched using a one-to-one propensity score method. The primary outcome was perioperative blood loss, calculated from patient blood volume and the difference in hemoglobin levels from preoperative to postoperative measurements. Results: Compared with 118 propensity score–matched patients undergoing TKA with medullary canal reaming of the femur, perioperative blood loss at 1, 3, and 7 days postoperatively was not significantly different in the 118 matched patients undergoing TKA without medullary canal reaming. In addition, no significant differences were observed in the requirement for allogeneic transfusion or the occurrence of deep venous thrombosis. Conclusions: Postoperative blood loss did not differ between patients who underwent TKA with femoral intramedullary reaming and those without. This study supports the notion that surgeons can use familiar surgical techniques, including conventional intramedullary rods, without the need for specialized instrument, even for patients at high risk of allogeneic transfusion.